1999
DOI: 10.1126/science.284.5415.757
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Nuclear Receptors: Shifting Endocrinology into Reverse

Abstract: Steroid and thyroid hormones and vitamin A metabolites (retinoids) regulate the expression of complex gene programs by binding to members of the nuclear receptor family of ligand-activated transcription factors. The nuclear receptor family also includes many "orphan" members that currently lack known ligands but that represent candidate receptors for new hormones. Recently, natural and synthetic ligands have been identified for several orphan receptors and used to dissect their biological roles. This "reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
295
0
8

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(304 citation statements)
references
References 58 publications
1
295
0
8
Order By: Relevance
“…The liver is a major target organ for estrogen action, so that the liver-abundant xenobiotic orphan nuclear receptors, CAR, or SXR, have the potential to modulate steroid hormone homeostasis (20). On one level, these nuclear receptors may regulate estrogen action by virtue of their induction of the cytochrome P-450 drug metabolizing enzymes that alter hepatic metabolism of estrogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver is a major target organ for estrogen action, so that the liver-abundant xenobiotic orphan nuclear receptors, CAR, or SXR, have the potential to modulate steroid hormone homeostasis (20). On one level, these nuclear receptors may regulate estrogen action by virtue of their induction of the cytochrome P-450 drug metabolizing enzymes that alter hepatic metabolism of estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the major organ that metabolizes steroids and one of the target organs for estrogen action in the body. ER␣ as well as these liver-enriched orphan receptors and their heterodimeric partner RXR are all expressed in the liver (20). Recent studies showed that the p160 coactivators, SRC-1, GRIP-1, and SRC-3, are expressed in the liver (21,22) and play a role in transcriptional activation mediated by the orphan receptors, CAR and SXR (16,23).…”
mentioning
confidence: 99%
“…Orphan nuclear receptors are members of the nuclear receptor family that lack identified ligands (27). Recent studies have identified several natural and synthetic ligands for orphan nuclear receptors, which led to new hormone-response systems implicated in the control of various aspects of development and adult physiology (28,29). Among orphan nuclear receptors, the estrogen-related receptors have been reported to be inhibited in their binding with coactivator protein by DES.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors have considerable overlap in their inducer profiles and can interchangeably bind to their respective response elements even across species boundaries (7). Interestingly, CAR, PXR and CXR belong to the family of orphan nuclear receptors comprising also receptors involved in cholesterol homeostasis, namely the oxysterol receptor LXR (liver X receptor) and the bile acid receptor (BAR, alternatively also designated FXR) (8). Moreover, all these receptors form heterodimers with the retinoid X receptor (RXR) for binding to their recognition sequences.…”
Section: Introductionmentioning
confidence: 99%